The Risk of Venipuncture in Newborn with Severe Hemophilia: Case Report of a Large Elbow Hemorrhage and Literature Review of Compartment Syndrome - Lassandro, Giuseppe; Amoruso, Anna; Palladino, Valentina; Palmieri, Viviana Valeria; Giordano, Paola (Hematology reports, 2021)
Hemophilias are hemorrhagic congenital rare diseases. The gold standard of therapy in hemophilics is the intravenously replacement therapy. We can infuse intravenously plasma derived factors (FVIII for Hemophilia A and FIX for Hemophilia B) or recombinant products (i.e., clotting factor synthetically produced). Venipuncture is not a safe procedure in subjects with hemorrhagic diseases. It is considered an invasive technique with potential massive bleeding and it requires standardized procedures to prevent complications. Local pressure after the procedure (with eventually ice rest) must be always done. In case of bleeding a rapid replacement therapy must be conducted. A severe complication in hemophilia is compartment syndrome. We report a case of massive bleeding in a hemophilic newborn after venipuncture and a literature review of compartment syndrome in hemophiliacs. The aim of this paper is to help physicians in the clinical management to prevent the evolution of a massive bleeding in compartment syndrome.